fMRI responses to words repeated in a congruous semantic context are abnormal in mild Alzheimer’s disease - Olichney, John M. (2010)
BACKGROUND: We adapted an event-related brain potential word repetition paradigm, sensitive to early Alzheimer’s disease (AD), for functional MRI (fMRI). We hypothesized that AD would be associated with reduced differential response to new/old congruous words. METHODS: Fifteen mild AD patients (mean age = 72.9) and 15 normal elderly underwent 1.5T fMRI during a semantic category decision task. RESULTS: We found robust between-groups differences in BOLD response to congruous words. In controls, the New > Old contrast demonstrated larger responses in much of the left-hemisphere (including putative P600 generators: parahippocampal, cingulate, fusiform, perirhinal, middle temporal (MTG) and inferior frontal gyri (IFG)); the Old > New contrast showed modest activation, mainly in right parietal and prefrontal cortex. By contrast, there were relatively few regions of significant New > Old responses in AD patients, mainly in the right-hemisphere, and their Old > New contrast did not demonstrate a right-hemisphere predominance. Across subjects, the spatial extent of New > Old responses in left medial temporal lobe (MTL) correlated with subsequent recall and recognition (r’s ≥ 0.60). In controls, the magnitude of New - Old response in left MTL, fusiform, IFG, MTG, superior temporal and cingulate gyrus correlated with subsequent cued recall and/or recognition (0.51 ≤ r’s ≤ 0.78). CONCLUSIONS: A distributed network of mostly left-hemisphere structures, which are putative P600 generators, appears important for successful verbal encoding (with New > Old responses to congruous words in normal elderly). This network appears dysfunctional in mild AD patients, as reflected in decreased word repetition effects particularly in left association cortex, paralimbic and MTL structures.